(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Serat Centhini written by Pakubuwana V in 1815 was transformed into a novel entitled Centhini: Kekasih yang Tersembunyi by Elizabet D. Inandiak in 2015. As a transformed work, the novel can be assured to contain different points (deviation and replacement) from Serat Centhini as a hypogram. There are things deviated in the novel Centhini: Kekasih yang Tersembunyi from the ones in Serat Centhini, like the differences of behaviors or actions of the characters. This study will discuss differences of actions taken by Tambangraras and Sheikh Amongraga in the episode empat puluh malam di pelaminan. This study aims to describe the differences of Tambangraras’ and Sheikh Amongraga’s actions in the novel Centhini and the ones in Serat Centhini. This study was derived from the theory of transformation by using a comparison technique. The data of this study was collected from an objective analysis of a hypogram and transformed work through observation and note-taking in a qualitative approach. In this regard, the actions and behaviors of Sheikh Amongraga and Tambangraras shown in Serat Centhini were compared to those shown in the novel Centhini: Kekasih yang Tersembunyi. From this study, it can be concluded that there are striking differences in terms of their behaviors and actions in the hypogram and the transformed novel. Consequently, readers cannot only rely on the transformed novel in understanding Serat Centhini. Both works must be viewed as different or independent work.